E-BOOKS UTILISATION AND STUDENTS' ACADEMIC ACHIEVEMENT IN UNIVERSITIES IN LAGOS STATE, NIGERIA: IMPLICATION FOR EDUCATIONAL PLANNERS - Gbesoevi, Emmanuel Semako; Ola, Bolanle Adeyemi; Oyelami , Monsurat Lolade; Jinadu, Oluwatosin Gabriel (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2022)
This study examined e-books utilisations and students' academic achievement in universities in Lagos State: implication for educational planners. With the use of descriptive survey research methodologies, this study was driven by three research questions and three null hypotheses. All six of Lagos State's traditional universities make up the study's population. Three institutions were chosen using a straightforward random sampling method. Additionally, 150 final-year students from each of the studied institutions were chosen using a practical selection approach, resulting in 450 respondents from the three universities chosen for the study. A well-structured questionnaire titled